2015
DOI: 10.1371/journal.pone.0134408
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for BRCA1 and BRCA2 Genetic Testing in an Asian Clinic-Based Population

Abstract: PurposeThe National Comprehensive Cancer Network (NCCN) has proposed guidelines for the genetic testing of the BRCA1 and BRCA2 genes, based on studies in western populations. This current study assessed potential predictive factors for BRCA mutation probability, in an Asian population.MethodsA total of 359 breast cancer patients, who presented with either a family history (FH) of breast and/or ovarian cancer or early onset breast cancer, were accrued at the National Cancer Center Singapore (NCCS). The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…High costs have long been cited as a barrier to entry for genetic testing internationally26 as well as locally 3 6. However, data gathered from our study showed that the relationship between cost and uptake rate is more complex than previously understood.…”
Section: Discussionmentioning
confidence: 68%
“…High costs have long been cited as a barrier to entry for genetic testing internationally26 as well as locally 3 6. However, data gathered from our study showed that the relationship between cost and uptake rate is more complex than previously understood.…”
Section: Discussionmentioning
confidence: 68%
“…A total of 28 novel potentially pathogenic variants were detected in BRCA1 , BRCA2 , PALB2 , TP53 , PTEN , NF1 , CDH1 , MSH6 and PMS2 ( Table 2 ) by our group in this study and previous studies. 4–6 …”
Section: Resultsmentioning
confidence: 99%
“…In the same study, the most common pathogenic BRCA2 variants were found to be c.3195_3198delTAAT (p.Asn1066Leufs*10) (n = 5) and c.5576_5579delTTAA (p.Ile1859Lysfs*3) (n = 5) in exon 11 [ 39 ]. The BRCA2 mutation c.7480C>T is enriched in Korean familial BC patients [ 49 ], and Wong et al reported four recurrent mutations in BRCA1 (p.Y1127* (c.3381T4A), E23Rfs*18 (c.67_68delinsAG), p.E1112Nfs*5 (c.3333delA), p.T1691K (c.5072C4)) and one BRCA2 mutation (p.C161W (c.483T4G)) in a population from Singapore [ 50 ]. In our hospital cohort, we detected one recurrent BRCA1 mutation (p.R1203X (c.3607C>T)) in one double cancer patient and in one OC patient without a family history ( Table 2 ), and the BRCA2 p.S1722fs (c.5164_5165 delAG) mutation was detected in two OC patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%